- ANALISIS PERTUMBUHAN DAN HASIL 3 VARIETAS TOMAT (Solanum lycopersicum) AKIBAT PEMBERIAN VARIASI PUPUK DALAM SISTEM POLIBAG - Elandika; Widata, Sri; Arnanto, Driska (Universitas Sarjanawiyata Tamansiswa, 2025)
ABSTRACTThis study aimed to analyze the growth and yield of three tomato varieties (Solanum lycopersicum) under different fertilizer treatments in a polybag system. The research was conducted at P4S “Lestari Makmur”, Sedayu, Bantul, using a Completely Randomized Design (CRD) with two factors: three tomato varieties (Servo, Permata, Betavila) and three fertilizer combinations (NPK + quail manure, NPK + cow manure, NPK + goat manure). A total of nine treatment combinations were tested with three replications. Observed variables included plant height, number of branches, stem diameter, number of clusters, number of flowers, number of fruits, fruit weight per plant, and fruit yield per hectare. The results showed no significant interaction between varieties and fertilizer types on all observed variables. However, the variety factor significantly affected plant height, number of branches, stem diameter, number of clusters, number of fruits per plant, fruit weight per plant, and fruit yield per hectare, while the number of flowers was not significantly different. Betavila variety showed superior vegetative growth, while Servo variety produced higher generative performance. Fertilizer types significantly affected the number of branches and clusters, with the combination of NPK + quail manure giving the best results. It can be concluded that Servo variety is more productive in terms of yield, while Betavila excels in vegetative growth. The application of NPK combined with organic manure, particularly quail manure, is recommended to enhance tomato growth and yield in polybag systems.Keywords: Tomato (Solanum lycopersicum), varieties, organic fertilizer, NPK, polybag